Bone quality in osteopenic postmenopausal women is not improved after 12 months of whole-body vibration training - Liphardt, Anna-Maria; Schipilow, J.; Hanley, D. A.; Boyd, S. K. (Osteoporosis international, 2015)
Whole-body vibration training may improve bone quality through structural adaptation. We tested if 12 months of training affects bone structure in osteopenic postmenopausal women by using advanced 3-dimensional high-resolution imaging techniques. We found that whole-body vibration training did not improve bone structure compared to inactive controls.Whole-body vibration training (WBVT) has been suggested as a preventive measure against bone loss. Contradicting results of previous studies may be confounded by insufficiently sensitive bone density measures to detect relevant bone changes. WBVT may improve bone quality through structural adaptations, without increasing bone mineral density (BMD). We hypothesized that 12 months of WBVT will improve or maintain bone microarchitecture and bone strength in osteopenic postmenopausal women.Twenty-two women received WBVT for 2-3 sessions/week and were compared with 20 controls. Bone outcomes were measured by high-resolution peripheral quantitative CT (HR-pQCT, XtremeCT, Scanco Medical) and finite element estimated bone strength. Balance and jump performance and maximum voluntary contraction (MVC) of knee flexor and extensor muscles were recorded. All measurements were taken at baseline, 4, 8, and 12 months and a reduced data set at 4 and 8 months follow-up and compared using a mixed model repeated measures ANOVA.Thirty-one women completed the study with 90 % compliance (WBVT: n = 17, control n = 14). Total BMD (p < 0.001), cortical area*(p = 0.004), cortical thickness (p = 0.011), and cortical porosity (p = 0.024) all significantly decreased over time in both groups; WBVT did not affect the response. All other bone outcomes were not affected by WBVT or time. No difference in measures of balance, jump height, and MVC due to WBVT were detected.In our cohort, WBVT did not lead to improved bone quality in postmenopausal osteopenic women after 12 months of training compared to controls, and there were no detected benefits related to balance and muscle strength outcomes.
EVALuna2:13502